Policy Reconstruction towards Justice Collaborator Determination of Corruption Cases based on Legal Certainty and Benefits Aspects - Setiyono Setiyono; Eriyantouw Wahid; I Komang Suka’arsana (CV. Ridwan Publisher, 2023)
One of the problems that sometimes arises in the law enforcement process in the eradication of corruption crimes is the problem related to determining the status as a witness for cooperating perpetrators or justice collaborators in solving a corruption case. The existence of several problems stemming from the inequality of understanding or not having unification of policies in determining the status of the perpetrator as a cooperating perpetrator witness or justice collaborator along with the benefits arising from the determination of the cooperating perpetrator witness or justice collaborator certainly creates legal uncertainty and also does not provide benefits or utility for the party who is determined as a cooperating perpetrator witness or justice collaborator. The reconstruction of the policy of establishing appropriate legal norms aims to regulate the recognition or recognition and understanding or perception of the same legally regarding the determination of the status of cooperating perpetrator witnesses or justice collaborators that apply from the examination stage at the investigation level to the examination stage at the court level even up to the implementation of its execution in order to create the principle of legal certainty for the Defendant who is designated as cooperating perpetrator witnesses or justice collaborators.